Quality of Psychopharmacological Medication Prescribing and Mortality in Medicare Beneficiaries in Nursing Homes. Issue 8 (15th July 2014) - Wei, Yu‐Jung; Simoni‐Wastila, Linda; Zuckerman, Ilene H.; Huang, Ting‐Ying J.; Brandt, Nicole; Moyo, Patience; Lucas, Judith A.
<x xml:space="preserve">Abstract</x> Objectives To examine the influence of quality measures of psychopharmacological medication (PPM) prescribing on all‐cause mortality in a Medicare long‐stay nursing home (NH) population. Design Longitudinal. Setting 2007–09 Medicare data linked to Minimum Data Set 2.0 files. Participants Four new‐user cohorts of residents initiating antipsychotic (n = 13, 105), antidepressant (n = 14, 251), anxiolytic and sedative–hypnotic (n = 10, 789), and any PPM (n = 14, 568) medication. Measurements Three measures of PPM prescribing quality were assessed monthly with a 6‐month look‐back: evidence of appropriate indication, dose (modified standardized daily dose (mSDD); below (<1), at (1), and above (>1) recommended geriatric dose), and duration of therapy (DOT; ≤30, 31–60, 61–90, 91–180 days from medication initiation). Complementary log–log models with quality measures as time‐dependent variables were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality. Results Appropriate use of antidepressants, anxiolytics and sedative–hypnotics, and any PPMs, as evidenced by appropriate indications, was significantly associated with lower mortality risk (HRantidepressants = 0.81, 95% CI = 0.76–0.86; HRanxiolytics and sedative–hypnotics = 0.81, 0.75–0.88; HRPPM = 0.89, 0.83–0.95). Antipsychotic and anxiolytic and sedative–hypnotic users with a mSDD of less than 1 had lower mortality risk than those with a mSDD greater than 1, whereas a protective effect was observed in antidepressant users with a mSDD greater than 1. In all four cohorts, those with a DOT of 91 to 180 days had lower mortality than those with a DOT of 1 month or less; the lower risk of mortality was detected after antipsychotic use for 31 days or longer. Conclusion Optimal PPM prescribing quality, as measured by indication and duration, is associated with low mortality. The benefit related to drug dosage varied by therapeutic class. When prescribing PPMs to NH residents, providers should consider not only drug choice, but also dose and duration of prescribed regimens.